Intratesticular Versus Intrafunicular Lidocaine to Reduce Perioperative Nociception and Immunological Response in Ponies Undergoing Field Castration - Cecilia Vullo; Rosalia Crupi; Rosanna Di Paola; Salvatore Cuzzocrea; Enrico Gugliandolo; Vito Biondi; Giuseppe Catone (Veterinary Sciences, 2022)
The aim of this study was to evaluate the impact of intratesticular or intrafunicular lidocaine to reduce perioperative nociception and cytokine release in ponies undergoing field castration under total intravenous anaesthesia. Before castration, one group was injected with intrafunicular (FL) lidocaine and the other received intratesticular (TL) lidocaine. All ponies were premedicated with acepromazine (0.05 mg/kg) intramuscularly. Twenty minutes after the administration of acepromazine, xylazine (1 mg/kg) and butorphanol (0.02 mg/kg) were administered intravenously. Lidocaine 2% was given 1 mL/100 kg intrafunicularly in the FL groups or 2 mL/100 kg intratesticularly on each testicular side for TL. Surgery was performed by the same team of two experienced surgeons using Serra’s emasculator and an open technique was used for all ponies in order to promote postoperative drainage. In this study, we focused on the plasmatic levels of TNF-α and IL-6. The results from this study showed a significant difference in plasmatic concentrations of TNF-α and IL-6 between the two different locoregional anaesthetic protocols. Taken together, the results suggest that the intrafunicular lidocaine locoregional anaesthesia could be a useful technique in the anaesthesia protocol for field pony castration.